‘I have to pretend that I don’t care’: Stigma management among unmarried young mothers in South-Western Nigeria - Ayomide Oluseye; Philippa Waterhouse; Lesley Hoggart (Global Public Health)
Young mothers often encounter stigma and discrimination, affecting their lives and that of their children. This paper explores stigma management strategies and their effectiveness for young mothers in rural Nigeria. Ten key informants and 24 young mothers were recruited from Ife-East in South-Western Nigeria. Data from semi-structured interviews showed that societal disapproval of pregnant teenagers and young mothers were common experiences. Women used a range of strategies to actively cope with stigma including: belief in predestination, avoidance, concealment, and cohabitation. These strategies could be seen as tools to mitigate negative stereotypes and discrimination. However, they also had the unintended consequences of compounding many young women’s difficult circumstances and exposing them to adverse outcomes, including gender-based violence, repeat pregnancies, poor mental health, and low uptake of services. The results show the need for policy frameworks to actively combat stigma by addressing the negative framing of early pregnancy and motherhood and promoting supportive environments for young mothers. Health professionals need to be trained to offer de-stigmatising services to encourage young mothers to seek help and reduce pre-existing inequities in access to services, and policies need to include measures that address the rights of young mothers and protect them from violence and abuse.